A numerical study of fixed bed reactor modelling for steam methane reforming process. (4th June 2015) - Rout, Kumar R.; Jakobsen, Hugo A.
Abstract A numerical comparison of the pseudo‐homogeneous, conventional heterogeneous, and simplified heterogeneous reactor models is performed for the steam methane reforming process. The pseudo‐homogeneous reactor model consists of a set of partial differential equations, where the diffusional limitations are accounted for by considering the effectiveness factor. The heterogeneous model is divided into two categories: conventional and simplified heterogeneous models. In the conventional heterogeneous model, there are separate equations for the fluid phase species mass balance, the fluid inside the catalyst pores. This is type of reactor model is needed when there is a considerable amount of inter‐phase mass transfer resistance present in the process. However, in the simplified heterogeneous reactor model the mass transport phenomenon is accounted for by accounting the efficiency factors. The model is validated against literature data. Several closures for the intra‐particle mass diffusion fluxes, the Maxwell–Stefan, Wilke, dusty gas, and Wilke–Bosanquet models, have been compared on the level of the catalyst pellet and the impacts of the different particle flux closures on the reactor performance are investigated. The simulations show that the conventional heterogeneous reactor model is necessary for the SMR process, because the effectiveness factor values of different reactions of the SMR process vary along the reactor axis. The maximum deviation between the pseudo‐homogeneous and the conventional heterogeneous reactor model is less than 38 %, whereas between the conventional and simplified heterogeneous reactor models it is less than 21 %. A parametric study of the transport phenomena on the pellet level is recommended prior to any large‐scale reactor simulation to determine what the rate determining transport mechanisms are.